Online Hedonic Consumers’ Privacy Concerns: A Systematic Literature Review - Ullah, G. M. Shafayet; Kumar, Sameer; Furuoka, Fumitaka (AEI Insights, 2023)
The purpose of this paper is to provide a comprehensive review of extant literature on online hedonic consumer’s various privacy related issues and in particular- the privacy concern. Further, the authors attempt to identify a gap that can be addressed in future through developing a comprehensive and integrated model on online hedonic consumer behaviour that focuses on their privacy concerns. The authors conducted a systematic literature review of the extant literature on online hedonic consumers, their various privacy related issues and in particular- the privacy concern. This paper, through its thorough literature review, made a clear distinction among privacy related issues that the online consumers face, namely privacy awareness. The discussion on “privacy concern” elucidated any confusions held by the researchers and readers. This review offered an insight into the current status of research in this field and recognized the factor “privacy concern” as a gap in the existing model on online hedonic consumer behaviour that could be properly explored in further scholarly empirical research. Exclusion of non-English language articles and lack of inclusion of different kinds of hedonic products or services other than SNSs were the limitation of this paper. Managers and e-commerce vendors could utilize the findings of this review to address their hedonic consumer’s privacy concern for the growth of their online businesses. This paper lays the groundwork to explore hedonic consumer’s privacy concern in detail. A new integrated model on online hedonic consumer behaviour is proposed, which provides a theoretical framework for researchers to further examine the mediation effect of privacy concern.